Hubungan Kadar Eosinofil dengan Derajat Hipertrofi Konka melalui Pemeriksaan Darah pada Pasien Rawat Inap di Rumah Sakit Umum Cut Meutia Aceh Utara - Inna Dwi Raisa; Zubir Zubir; Baluqia Iskandar Putri (Jurnal Ilmu Kesehatan dan Gizi, 2026)
Turbinate hypertrophy is a condition characterized by abnormal enlargement of the nasal turbinate mucosa, which can lead to chronic nasal obstruction and decreased quality of life. This condition is associated with inflammatory processes in which eosinophils play a role as part of the immune response. This study aimed to determine the relationship between eosinophil levels and the degree of turbinate hypertrophy based on blood examination in hospitalized patients. This research used an observational analytic design with a cross-sectional approach involving 40 patients diagnosed with turbinate hypertrophy at Cut Meutia General Hospital, North Aceh. Data were obtained from medical records, including patient characteristics, eosinophil levels, and the degree of turbinate hypertrophy. The results showed that most patients were aged 17–25 years, predominantly female, and commonly had non-allergic underlying conditions. The majority of patients had normal eosinophil levels (80%), while most cases were classified as grade III turbinate hypertrophy (65%). Statistical analysis using Fisher’s Exact Test demonstrated no significant relationship between eosinophil levels and the degree of turbinate hypertrophy (p>0.05). These findings suggest that eosinophil levels may not be a reliable indicator in assessing the severity of turbinate hypertrophy, particularly in patients with non-allergic conditions. This study highlights the need to consider other contributing factors in the evaluation and management of turbinate hypertrophy to improve diagnostic accuracy and treatment outcomes.